When sports rules go awry - Kendall, G.; Lenten, Liam J.A. (Elsevier, 2017)
Wright (Wright, M. OR analysis of sporting rules - A survey. European Journal of Operational Research, 232(1):1-8, 2014) recently presented a survey of sporting rules from an Operational Research (OR) perspective. He surveyed 21 sports, which consider the rules of sports and tournaments and whether changes have led to unintended consequences. The paper concludes: "Overall, it would seem that this is just a taster and there may be plenty more such studies to come". In this paper we present one such study. This is an interdisciplinary paper, which cuts across economics, sport and operational research (OR). We recognize that the paper could have been published in any of these disciplines but for the sake of continuity with the paper that motivated this study, we wanted to publish this paper in an OR journal. We look at specific examples where the rules of sports have led to unforeseen and/or unwanted consequences. We hope that the paper will be especially useful to sports administrators, helping them to review what has not previously worked and also encouraging them to engage with the scientific community when considering making changes. We believe that this is the first time that such a comprehensive review of sporting rules, which have led to unexpected consequences, has been published in the scientific literature.